2023
DOI: 10.1108/ijwbr-06-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Wine label design proposals: an eye-tracking study to analyze consumers’ visual attention and preferences

Abstract: Purpose The main purpose of this study is to analyze how consumers’ visual attention to wine label design correlates with their preferences. Accordingly, this study uses quantitative eye-tracking metrics to understand which design proposal has greater visual salience. A more specific objective was to assess which design proposal was preferred to be marketed. Design/methodology/approach The experiment involved evaluating of three different labeling proposals of an Italian winery. Infrared eye-tracking was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Moreover, referring to the implications of the cognitive neuromarketing model, based on the participants' observation of the selected DeFi social media profile, important insights arise. Firstly, from the heatmaps and gazes of the participants (Figure 5) [72], it is shown that they expressed much interest in the DeFi social media profile by intensely observing the links to other websites provided in specific places on the profile page [75]. Moreover, the participants were keen on reading the "You might like" and "Who to follow" columns of the DeFi social media profile, which indicates the influence the profile has on visitors who might be searching for some information [76].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, referring to the implications of the cognitive neuromarketing model, based on the participants' observation of the selected DeFi social media profile, important insights arise. Firstly, from the heatmaps and gazes of the participants (Figure 5) [72], it is shown that they expressed much interest in the DeFi social media profile by intensely observing the links to other websites provided in specific places on the profile page [75]. Moreover, the participants were keen on reading the "You might like" and "Who to follow" columns of the DeFi social media profile, which indicates the influence the profile has on visitors who might be searching for some information [76].…”
Section: Discussionmentioning
confidence: 99%
“…The experiment duration was 10 minutes in total. Eye tracking data was collected using Pupil Labs Invisible eyeglasses, which has been used in similar studies [39,40].…”
Section: Studymentioning
confidence: 99%
“…Visualizar as informações nas embalagens de alimentos é um pré-requisito necessário para utilizá-las. A capacidade dos consumidores localizarem as informações nutricionais, passou a ser monitorada por meio de equipamento de rastreamento ocular, conhecido como Eye Tracking (DELIZA et al, 2016;MEYERDING & MERZ, 2018;OLIVEIRA, 2019;MOTOKI, SAITO & ONUMA, 2021;BARBIERATO et al, 2023). Esta técnica tem como princípio investigar a atenção visual do usuário por meio da gravação do trajeto ocular, para definir quais imagens, objetos, frases ou outros elementos visuais que apresentados, despertaram sua atenção (KLAIB et al, 2021).…”
Section: )unclassified
“…Assim, estudos têm sido desenvolvidos para avaliar o efeito dos atributos das embalagens sobre o comportamento do consumidor. Características não sensoriais, como, por exemplo, as in-formações nutricionais influenciam a intenção de compra, a aceitação ou escolha do produto pelo consumidor (BANDEIRA et al, 2021;ALCÂNTARA, ARES & DELIZA, 2022;BARBIERATO et al, 2023;MINIM, 2023). Em vista disso, a busca por métodos inovadores que auxiliem numa maior compreensão das influências das características não sensoriais na avaliação dos consumidores é crescente, sendo o rastreamento ocular (eye tracking) e a análise conjunta de fatores (conjoint analysis) duas dessas ferramentas.…”
Section: Introductionunclassified